The assessment of vitamins and cholesterol amounts in gill and muscle tissues of Clarias Gariepinus using HPLC - Dayangac, Alpaslan; Akyildiz, Gulender; Akkoyun, H. Turan; Bahsi, Muammer; Aktas, Taylan; Ciftci, Harun; Yilmaz, Okkes (Elsevier Sci Ltd, 2013)
[Abstract Not Available]
European Biotechnology Congress -- MAY 16-18, 2013 -- Comenius Univ, Bratislava, SLOVAKIA